1981
DOI: 10.1159/000123193
|View full text |Cite
|
Sign up to set email alerts
|

Estrous Behavior and Pituitary and Brain Cell Nuclear Retention of [<sup>3</sup>Η]Estradiol in Chronically Insulin-Deficient Female Rats

Abstract: Chronic insulin deficiency, produced by administration of 60 mg/kg streptozotocin, leads to reduced estrous behavior and lower estradiol uptake in both whole homogenate and cell nuclear fractions of hypothalamus-preoptic area and pituitary gland in ovariectomized rats. High dietary fat intake produces an ameliorative effect on both lordosis behavior and estradiol uptake, relative to animals fed a standard, carbohydrate-rich diet. Plasma glucose levels are significantly correlated with estradiol uptake levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…It is likely that rats that are chronical ly deprived of insulin provide a more useful metabolic mod el for the study of reproductive dysfunction in diabetics. We have found that mildly diabetic female rats with chronic in sulin deficiencies show deficits in estradiol uptake in brain and pituitary, as well as deficits in sex behavior, that are ameliorated by high dietary fat [7], Further experiments will be necessary to clarify the mechanism by which insulin defi ciency modulates estradiol uptake in the central nervous system, and to determine whether simple starvation affects estradiol uptake in brain and pituitary in nondiabetic ani mals. We can conclude from the present results that the es tradiol uptake deficits in brain and pituitary gland in acute ly insulin-deprived rats are slow to develop and seem to re sult indirectly form the general alterations in the metabolic condition of the animal, and that these deficits are likely to be related to reproductive dysfunction.…”
Section: Discussionmentioning
confidence: 90%
“…It is likely that rats that are chronical ly deprived of insulin provide a more useful metabolic mod el for the study of reproductive dysfunction in diabetics. We have found that mildly diabetic female rats with chronic in sulin deficiencies show deficits in estradiol uptake in brain and pituitary, as well as deficits in sex behavior, that are ameliorated by high dietary fat [7], Further experiments will be necessary to clarify the mechanism by which insulin defi ciency modulates estradiol uptake in the central nervous system, and to determine whether simple starvation affects estradiol uptake in brain and pituitary in nondiabetic ani mals. We can conclude from the present results that the es tradiol uptake deficits in brain and pituitary gland in acute ly insulin-deprived rats are slow to develop and seem to re sult indirectly form the general alterations in the metabolic condition of the animal, and that these deficits are likely to be related to reproductive dysfunction.…”
Section: Discussionmentioning
confidence: 90%
“…Many of these nuclei play a role in reproductive behavior [13, 24, 25, 26]. Insulin may regulate female reproductive function in both nondiabetic and diabetic animals by maintaining hypothalamic responsiveness to estrogen [16, 27, 28, 29, 30]. Estrogen regulation of reproductive behavior involves hormone binding to hypothalamic estrogen receptors and retention of the ligand-receptor complex in the cell nucleus [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes has been shown to reduce estrogen receptor binding and diminish retention of nuclear estrogen receptors in the hypothalamus. Moreover, peripheral injection of insulin can prevent the diabetes-induced reduction in hypothalamic estrogen receptor levels [16, 27, 28, 29, 30]. Support for the notion that insulin may be directly responsible for decreased nuclear estrogen receptor binding has been reported in diabetic animals [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes leads to deficits in the neuroendocrine regulation of reproductive physiology [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17]. For example, diabetes reduces the ability of estrogen to facilitate the display of female reproductive behavior [1, 2, 3, 4, 5, 6] and also leads to aberrant ovarian hormone regulation of luteinizing hormone release [7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, diabetes reduces the ability of estrogen to facilitate the display of female reproductive behavior [1, 2, 3, 4, 5, 6] and also leads to aberrant ovarian hormone regulation of luteinizing hormone release [7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17]. Despite these observations, little is presently known about the neurochemical basis underlying these diabetes-induced deficits in reproductive physiology.…”
Section: Introductionmentioning
confidence: 99%